Types, structure and potential for axial water flow in the deepest roots of field-grown cereals - Watt, Michelle; Magee, Linda J.; McCully, Margaret E. (The New phytologist, 2008)
Deep root systems that extend into moist soil can significantly increase plant productivity. Here, the components of soil-grown root systems of wheat, barley and triticale are characterized, and types and water conducting potential of deep roots in the field are assessed. Root system components were characterized in plants grown in soil in PVC tubes, based on their origin and number and the arrangement of xylem tracheary elements (XTE) viewed using fluorescence microscopy. A new nomenclature is proposed. Deep roots were harvested in the field, and root types of the current crop and remnant roots from previous crops were identified by fluorescence and cryo-scanning electron microscopy. Four types of axile (framework) and five types of branch root were distinguished in the three cereals. Six per cent of deep roots were axile roots that originated from the base of the embryo; 94% were branch roots, of which 48% had only two XTE (10 μm diameter), and thus potentially low axial flow. Only 30% of roots in the cores were from the current crop, the remainder being remnants. Selection for more deep-penetrating axile roots and increased vascular capacity of deep branches is of potential benefit. Conventional root-length density measurements should be interpreted and applied cautiously.